A Critical View on Morality and Professional Ethics - Murat Yılmaz (Türk Kütüphaneciliği)
Morality is a tool to decide to help what good and right or bad and wrong is. As for professional ethics, it guides what the appropriate behaviors performed by librarians are. The aim of this research is to explicate morality and professional ethics from a critical view.